The cost of preoperative urodynamics: A secondary analysis of the ValUE trial. Issue 1 (18th October 2014) - Norton, Peggy A.; Nager, Charles W.; Brubaker, Linda; Lemack, Gary E.; Sirls, Larry T.; Holley, Robert; Chai, Toby C.; Kraus, Stephen R.; Zyczynski, Halina; Smith, Bridget; Stoddard, Anne
Abstract: Aims: Urodynamic studies (UDS) are generally recommended prior to surgical treatment for stress urinary incontinence (SUI), despite insufficient evidence that it impacts treatment plans or outcomes in patients with uncomplicated SUI. This analysis aimed to calculate the cost incurred when UDS was performed as a supplement to a basic office evaluation and to extrapolate the potential savings of not doing UDS in this patient population on a national basis. Methods: This is a secondary analysis from the Value of Urodynamic Evaluation (ValUE) trial, a multicenter non‐inferiority randomized trial to determine whether a basic office evaluation (OE) is non‐inferior in terms of SUI surgery outcomes to office evaluation with addition of urodynamic studies (UDS). All participants underwent an OE; those patients who randomized to supplementary UDS underwent non‐instrumented uroflowmetry, filling cystometry, and a pressure flow study. Costs associated with UDS were calculated using 2014 U.S. Medicare allowable fees. Models using various patient populations and payor mixes were created to obtain a range of potential costs of performing UDS in patients undergoing SUI surgery annually in the United States. Results: Six hundred thirty women were randomized to OE or OE plus UDS. There was no difference in surgical outcomes between the two groups. The per patient cost of UDS varied from site to site, and included complex cystometrogram $314–$343 (CPT codes 51728–51729) plus complex uroflowmetry $16 (CPT code 51741). Extrapolating these costs for US women similar to our study population, 13–33 million US dollars could be saved annually by not performing preoperative urodynamics. Conclusion: For women with uncomplicated SUI and a confirmatory preoperative basic office evaluation, tens of millions of dollars US could be saved annually by not performing urodynamic testing. In the management of such women, eliminating this preoperative test has a major economic benefit. Neurourol. Urodynam. 35:81–84, 2016 . © 2014 Wiley Periodicals, Inc.